The spectrum of Gl ischemia 2 - Brandt, Lawrence J. (Henry Stewart Talks, 2022)
AMI (Acute mesenteric ischemia) testing and imaging, AMI risk factors and therapy, Focal segmental ischemia, Mesenteric artery occlusive disease, SMA thrombus, Mesenteric venous thrombosis, Mesenteric artery stenosis